1997
DOI: 10.1002/(sici)1099-0496(199703)23:3<198::aid-ppul5>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspiration of milk on mechanisms of neural control in the airways of developing rabbits

Abstract: We studied the effects of recurrent aspiration of milk on neural control of airways in young developing rabbits. Beginning at 1 week of age, rabbits received 0.5 ml/kg of whole milk or sterile physiologic saline intranasally while under light methoxyflourane anesthesia 5 days a week for a period of 3 weeks. At 4 and 8 weeks of age, in vitro studies of contractile and relaxant responses of tracheal smooth muscle (TSM) segments were evaluated. To assess the neurally mediated contractile responses, frequency resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…Similar findings have also been reported with aspiration and airway dysfunction. [25][26][27] Similar to the findings in this study, in some earlier studies, we have shown improvement of asthma outcomes in children with asthma and GERD, with the use of anti-GERD treatment. [8][9][10][11][12][13][14] Subsequent studies by other workers have supported our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings have also been reported with aspiration and airway dysfunction. [25][26][27] Similar to the findings in this study, in some earlier studies, we have shown improvement of asthma outcomes in children with asthma and GERD, with the use of anti-GERD treatment. [8][9][10][11][12][13][14] Subsequent studies by other workers have supported our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Aspiration can also have longterm effects such as food protein sensitization, abnormal neural control, increased reactivity of airways, and chronic airway dysfunction. 2,3 Additionally, aspiration could have the potential of worsening the course of bronchiolitis in an otherwise clinically stable infant with RSV bronchiolitis. We studied the possible association of aspiration with rapid clinical deterioration in previously healthy infants with RSV bronchiolitis, using the lipidladen macrophage index (LLMI) as a marker.…”
Section: Introductionmentioning
confidence: 99%
“…32 By using this tact, it has been noted that various insults (allergen sensitization, respiratory syncytial virus infection, and aspiration) early in postnatal development can alter the normal balance of neural control within an airway toward a hyperresponsive pattern for prolonged periods of time. 25,26,33 Observations such as these have been made not only within the laboratory of authors of this review (GLL and J-KBK) but also by other investigators with an interest in the importance of the stage of development on the outcome of a pulmonary insult. For example, studies with parainfluenza type 1 virus (Sendai) showed neonatal infection of genetically susceptible rats led to chronic abnormalities in airway morphology, histology, and physiology.…”
Section: Models Of Airway Dysfunction In Developing Speciesmentioning
confidence: 85%